Gender-matching school effects on girls' cognitive and non-cognitive performance: Empirical evidence from South Korea - Seo-Young Cho (Philipps-University Marburg, School of Business and Economics, 2017)
Gender-matching school environments may provide benefits for girls to enhance their performance. By using PISA data from South Korea, this paper suggests that the effects of single-sex schooling and a student-teacher's gender matching are heterogeneous across different student groups. The gender-matching school environments are most positive to non-cognitive outcomes of girls at the highest tail of cognitive performance levels. By attending an all-girls school and being taught by a female teacher, high performing girls are as motivated and interested in pursuing careers in STEM fields as boys. However, single-sex schooling and female teachers do not produce positive effects on girls in lower performing groups. For median girls, single-sex schooling can even be detrimental to their non-cognitive performance. These results corroborate that gender-matching school environments can be a useful tool to promote female talent in STEM fields, but the effect cannot be generalized for public education for all students.
Keywords: C31; I21; I24; J16; O53; 330; gender-matching effects; student-teacher's gender-matching; single-sex schooling; cognitive performance; non-cognitive performance; education production functions; propensity-score matching; South Korea